Architecture and Transgression: An Interview with Bernard Tschumi. (November 2013) - Mosley, Jonathan; Sara, Rachel; Mosley, Jonathan; Sara, Rachel
Abstract Almost four decades ago, the influential architect and educator Bernard Tschumi wrote the seminal manifesto 'Architecture and Transgression'. Here, Guest‐Editors Jonathan Mosley and Rachel Sara revisit with Tschumi his original thesis, investigating how his thinking has evolved around transgression and its aptness for the world today.